(untitled) (Религиски дијалог и соработка, 2020)
Many social theorists accept the idea that secularization is a simple, inherent, linear process leading to progress, modernization, and development. Adopting what is variously called traditional religion, religious extremism, or fundamentalism is considered to be like other forms of “irrationalism”. On the other hand, the global resurgence of religion can be seen as part of the larger crisis of modernity. The resurgence of religious faith is a type of cultural critique of the kind of world modernity has brought us. Religion provides safety. Modern society is a society of risk. De-privatization of religion and its reemergence on the public scene as a consequence of its role to solve the dissatisfaction with modernization effects. Religion finds a new social role here – that of suggesting that society is moving in the wrong direction. The return to the sacred/religion is through the satisfaction of two needs, which are a part of the conditio humana: security and meaning. De-privatization is the repeated influence of religion on secularized domains and politics. Religion finds roles to play in generating policy decisions, mobilizing moral commitments, defending human rights, legitimating ethnic or national identities, instilling work ethics, and otherwise influencing sociocultural affairs. Religion also involves into new forms like the one of cultural defense, preventing national, ethnic, local or other culture from decay/vanishing in the era of global identities. This reality imposes the need of including the religion in the intercultural dialogue as a way of securing peace and cooperation.